2019
DOI: 10.3390/toxins11030148
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Induced by Bothrops Venom: Insights into the Pathogenic Mechanisms

Abstract: Acute kidney injury (AKI) following snakebite is common in developing countries and Bothrops genus is the main group of snakes in Latin America. To evaluate the pathogenic mechanisms associated with Bothrops venom nephrotoxicity, we assessed urinary and blood samples of patients after hospital admission resulting from Bothrops snakebite in a prospective cohort study in Northeast Brazil. Urinary and blood samples were evaluated during hospital stay in 63 consenting patients, divided into AKI and No-AKI groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 44 publications
1
37
0
11
Order By: Relevance
“…Studies reported slight increase of creatine phosphokinase level in Bothrops envenoming [14,66]. The local muscle injury caused by Bothrops venom could contribute to AKI.…”
Section: Myoglobinuriamentioning
confidence: 98%
See 4 more Smart Citations
“…Studies reported slight increase of creatine phosphokinase level in Bothrops envenoming [14,66]. The local muscle injury caused by Bothrops venom could contribute to AKI.…”
Section: Myoglobinuriamentioning
confidence: 98%
“…There are several epidemiological studies that describe AKI. However, only a few applied the AKI definition according to KDIGO, AKIN or RIFLE criteria [5,8,11,14,56,[67][68][69][70][71][72][73][74]. Data from retrospective series described a great variable in AKI incidence, 1.4 to 44.4% [5,8,11,56,[66][67][68][69][70][71][72][73][74].…”
Section: Incidence Of Aki Following Bothrops Envenomingmentioning
confidence: 99%
See 3 more Smart Citations